Proceso de atención de enfermería en un niño de 5 meses de edad con neumonía bacteriana - Gómez Naranjo, Fernanda (2018)
The Nursing Care Process is a tool of great importance for the nursing staff as it helps us identify the altered needs, correct, maintain and rehabilitate the patient by means of theoretical and practical knowledge, in order for the patient to recover his health status, this case study was applied in a 5-month-old boy diagnosed with bacterial pneumonia. Bacterial pneumonia is one of the main causes of death in children less than 5 years old, causing an affectation to the pulmonary alveoli, which compromises the respiratory pattern. This pathology if not treated in a timely manner can cause complications such as a pleural effusion, empyema, atelectasis, etc. Its diagnosis only occurs through clinical examinations. For the nursing staff it is very important to know about the care provided to these patients to reduce the number of children with respiratory problems in Ecuador. We identified the basic needs of the human being based on the fourteen needs of Virginia Henderson since this model is the one that most couples the pediatric patients by their level of dependence; with the help of the taxonomies of NANDA, NIC and NOC, a timely nursing diagnosis could be made and thus create a care plan prioritizing their symptomatology. The results obtained were satisfactory, decreased respiratory difficulty, improvement in airway patency, maintaining vital signs without alteration.